PENYISIHAN AMONIAK DAN KEKERUHAN PADA SISTEM RESIRKULASI BUDIDAYA KEPITING DENGAN TEKNOLOGI MEMBRAN BIOFILTER - Malida Fauzzia; Izza Rahmawati; I Nyoman Widiasa (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2013)
Crabs are one of the economically valuable commodities. Barriers that often occur in crab farming in ponds is limited land and water. Crab aquaculture activities can not be apart from the waste generated, which can cause water quality degradation, especially of food remains, feases and the metabolism of the crabs. Waste produced as ammonia is toxic at high concentrations and high turbidity can cause death in the crabs. Alternative technologies are used to decrease the production of crabs due to lack of availability of  land and water degradation are water recirculation system using a membrane biofilter. Membrane biofilter is used to maintain the water quality is to eliminate ammonia to levels not exceeding 0.1 ppm, and removing turbidity to <30 NTU.  Biofilter  is used to eliminate ammonia by nitrification and denitrification process using aerobic and anaerobic mikrroorganisme. Membranes which is used to reduce turbidity is ultrafiltration membranes. Flux on the membrane will determine the performance of the membrane. If  the flux decreased 85% from the initial flux, indicating the occurrence of fouling on membrane. This fouling can be overcome by washing. One of  it is the backwash. Using biofilter can reduce of ammonia from 4,41 mg/L up to 1,48 mg/L during 7 days. Turbidity can be reduced by using ultrafiltration membrane. In the Ultrafiltration membrane fouling control can be done by backwash 30 minutes 15 seconds. This is indicated by the high flux of the membrane.